PENERAPAN INTEGRATED FARMING SYSTEM (IFS) MENUJU DESA AGROWISATA DI DESA JATISARI, KECAMATAN JATISRONO, KABUPATEN WONOGIRI - Rachmawatie, Srie Juli; Respati, Adib Norma; Oktyajati, Nancy; Widiastuti, Libria; Rahayu, Endang Siti; Sutrisno, Joko (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2021)
Integrated Farming System is a management system for plants, livestock, and aquaculture with environment to produce an excellent product. The objectives of the community service activity were empowering Jatisari Village community to realize the Agrotourism Village, ensuring integrated farming systems run well and optimally, and making Jatisari Village a fostered village of the Faculty of Engineering, Science and Agriculture UNIBA. Integrated farming system is a system that combines agricultural activities, animal husbandry, fisheries, and forestry with other sciences related to agriculture in one land, so that it is expected to be one of the solutions for increasing land productivity, building programs and environmental conservation, and integrated village development. Entrepreneurship is also important to support the existence of agrotourism of Jatisari Village. Jatisari Village is prospective in developing agrotourism areas. Local potential, natural resources and human resources can be utilized to support the development of agrotourism areas